EFEKTIVITAS PEDOMAN ‘PEMAHAT ASIK’ TERHADAP PERILAKU ANAK DAN ORANGTUA DALAM MENCEGAH MASALAH STATUS GIZI - Puspita, Luh Mira; Karin, Putu Ayu Emmy Savitri (Coping: Community of Publishing in Nursing; Vol 11 No 3 (2023): Juni 2023DO - 10.24843/coping.2023.v11.i03.p12, 2023)
The national prevalence of obesity problems in children aged 6-12 years is still categorized as high. Obesity will cause health problems in school-age children, around 20-30% of children suffer from hypertension, type 2 diabetes mellitus, and sleep apnea. Factors that influence the occurrence of overweight in children are eating behavior and physical activity. Eating behavior and activities are influenced by children's knowledge, eating habits, and environmental factors. Children who have light physical activity have a 3 times greater risk factor for obesity. Providing health education can increase understanding of healthy eating behavior and optimizing physical activity. This study aimed to analyze the effectiveness of implementing dietary and physical activity behavior guidelines on obesity prevention behavior. The research method used pre-experimental design with a one group pretest-posttest design. The population in this study were parents of students in grades 4-6. The sampling technique was carried out using probability sampling, namely total sampling. Questionnaire used in this study was modifications from Food Frequency Questionnare and Adolescent Sedentary Activity Questionnare. The bivariate analysis was carried out using the nonparametric Wilcoxon Test. The research results showed a p-value < 0,05 so that providing guidelines for healthy eating behavior and physical activity was effective in changing the behavior of children and parents in preventing nutritional status problems. The teachers is expected to provide regular education to students so that nutritional status problems can be resolved.